The Abundance and Persistence of Temperate and Tropical Seagrasses at Their Edge-of-Range in the Western Atlantic Ocean - Bartenfelder, Amy; Kenworthy, William Judson; Puckett, Brandon; Deaton, Charles; Jarvis, Jessie C. (Frontiers in Marine Science, 2022)
Species, including seagrasses, at their range limits are uniquely vulnerable to climate change. In the western Atlantic Ocean, the biogeographic transition zone between temperate and tropical ecosystems is recognized as one of several global hotspots where poleward-flowing western boundary currents are forecast to warm faster than the global average. In this region seagrass ecosystem services are primarily supplied by two species, Zostera marina, a temperate seagrass at its southern range limit and Halodule wrightii, a tropical seagrass at its northern limit. Water temperatures in the study location in Back Sound, North Carolina, USA have gradually increased the length of the stressful summer season for Z. marina (beginning after 3 consecutive days of daily mean water temperatures >23°C, ending after 3 consecutive days <25°C) from 84 days in 1962 to 156 days in 2019. The occurrence of extreme water temperatures also increased resulting in temperatures ≥30°C occurring more frequently in the last decade (2009-2019) than the previous 10 years. Biomass and aerial imagery collected periodically from 1981-2019 indicate that Z. marina biomass remained stable until 2008 but declined to 30-year low levels by 2019. Meadow area estimated from imagery collected during peak Z. marina biomass did not show a significant trend over time; however, lowest meadow area during the time series was recorded in 2019. Despite summer warming, H. wrightii biomass remained steady between 1979-2019 but did not replace Z. marina as the dominant species in the cooler months. We hypothesize that persistence of temperate Z. marina populations under stressful water temperatures is positively influenced by water clarity, life history, and meadow stability, due in part to the consistent presence of tropical H. wrightii maintaining meadow biomass and area. However, temperate species in edge-of-range tropicalized meadows, are still limited by physiological thresholds, and when these limits are exceeded, related declines in meadow biomass and area may not be fully replaced by tropical species immediately. Therefore, while tropicalization of seagrass meadows may result in greater resilience to abiotic stressors in the short-term, declines in biomass and area during the process of tropicalization may have significant impacts on meadow function.